STRATEGI GURU DALAM MENDISIPLINKAN BELAJAR SISWA KELAS VA DI SD NEGERI 21 PEKANBARU - Septi Etika Rahmi; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine teachers' strategies in disciplining student learning in elementary schools. This research uses a qualitative descriptive method approach. Primary data sources in research are teachers, students and school principals. Meanwhile, secondary data sources in this research are books and articles as well as supporting previous research. The data collection techniques used were interviews using interview sheets and observations using observation sheets. The data analysis technique in this research is Miles and Huberman which consists of data collection, data reduction, data presentation, and drawing conclusions. The strategies used by teachers to discipline student learning are through regulations, punishments and rewards and example. Overall, it can be concluded that the integration of indicators such as rules, punishment, rewards, and example work together to create a disciplined and motivating learning environment for students.